Pragmatic use of short‐course radiotherapy, chemotherapy and surgery for stage IV rectal cancer with locally advanced or symptomatic primary tumours. Issue 7 (31st August 2021) - Higgins, Martin J; Mulsow, Jurgen; Staunton, Oonagh; Aird, John; Cronin, Carmel; Dunne, Mary T; Burke, John; Shields, Conor; Faul, Eleanor; McCawley, Niamh; Toomey, Des; Conneely, John; et al.
Abstract: Introduction: We assessed management of patients with de novo metastatic rectal cancer, referred for radiotherapy to the rectum, who were candidates for short‐course radiotherapy (SCRT) and chemotherapy, followed by resection of all disease. We assessed surgical outcomes, overall survival (OS) and progression‐free survival (PFS). Methods: Retrospective review of patients meeting criteria: (i) treatment with SCRT to rectum; (ii) locally advanced primary rectal cancer; and (iii) resectable distant metastases at diagnosis. Data were collected from charts, correspondence and electronic patient records. OS and PFS were calculated using the Kaplan–Meier method. Results: Between 2016 and 2020, 48 patients with stage IV rectal cancer at diagnosis were treated with SCRT. Only 15 patients (31%) had resectable metastatic disease and were intended for SCRT (25 Gy/5#), then chemotherapy, followed by resection of all sites of disease and are included in our study. 12 of the 15 surgical candidates (80%) had rectal surgery as planned, and 11 of the 15 (73%) had resection of the rectal primary and all metastatic disease. One patient had a pathological complete response (pCR), and 50% of surgical patients had a Mandard TRG of 1 or 2. Median PFS and OS for the 15 surgical candidates were 12.6 and 25.2 months, respectively, with a median FU of 21.2 months. Conclusion: For this cohort of patients, our treatment paradigm is pragmatic and results in excellent pathological response. However, the effectiveness of this approach should be the subject of future prospective studies.